Volume and Heat Transports by North Brazil Current Rings - Bueno, Luana F.; Costa, Vladimir S.; Mill, Guilherme N.; Paiva, Afonso M. (Frontiers in Marine Science, 2022)
A methodology that combines a 24-year long (January 1993 to December 2016) global dataset of eddy trajectories, derived from altimetry, with vertical temperature and salinity profiles from the EN4.2.0 database, derived from XBTs/MBTs, CTDs and Argo floats, was used to reconstruct the mean vertical structure of North Brazil Current (NBC) rings, and to calculate some of their properties. The number of NBC rings formed each year varied from 2 to 8, with an annual-mean formation of 5.3 ± 1.5. During the analyzed period, 112 rings were sampled at least once, at various distances from the center of the rings, leading to a total of 1323 (604) temperature (salinity) profiles available to compute the mean NBC ring, depicting a large, surface intensified, and relatively shallow ring, with intense temperature and salinity anomalies. The meridional volume transport was estimated in 1.3 Sv (1Sv = 106 m3s-1) per ring, leading to an annualized transport of 7 ± 2 Sv. The amount of South Atlantic Water (SAW) within the mean ring was estimated in 40 to 60% of the ring volume. According to these estimates, NBC rings may be responsible in different years for approximately 20 to 80% of the northward volume transport associated with the upper limb of the Atlantic Meridional Overturning Circulation (AMOC), and approximately 15 to 55% of the meridional heat transport in the tropical Atlantic.